Loner or socializer? Ravens’ adrenocortical response to individual separation depends on social integration - Stocker, Martina (Horm Behav, 2015)
Non-breeding common ravens (Corvus corax) live in complex social groups with a high degree of fission–fusion dynamics. They form valuable relationships and alliances with some conspecifics, while taking coordinated action against others. In ravens, affiliates reconcile their conflicts, console each other after conflicts with a third party, and provide each other with social support — all behaviors that presumably reduce corticosterone levels and alleviate stress. However, how well an individual is socially integrated in a (sub)group might vary substantially. This raises the question whether the social integration of a raven affects its stress responses to fission–fusion dynamics. The present study aims to investigate this effect experimentally by separating single ravens (n = 16) individually from their group for four days and subsequently reintroducing them. To determine stress response patterns in the separated individuals we measured the amounts of immunoreactive corticosterone metabolites (CM) in droppings. We compared two enzyme immunoassays, which we validated by conducting an ACTH challenge, and finally decided to apply an 11-oxoetiocholanolone enzyme immunoassay. Additionally, we determined levels of social integration using focal observations. Our findings suggest that a strong social integration is related to low CM levels when the individuals are within the group and high levels during separations, implying that separation leads to stress in these birds. In contrast, poorly socially integrated ravens seem to exhibit the opposite pattern, indicating that to them group living is more stressful than being temporarily separated. We, therefore, conclude that the birds’ adrenocortical activity is modulated by their social integration.